Evolution of strategy approaches in management: the journey from the industry vision to the resource-based approach. - RABAH–RABBOU, Mounir; EL ADRAOUI, Fatima Ezzahra; DIDI SEDDIK, Mohamed Mouad; JABBOURI , Jihad (African Scientific Journal, 2024)
Abstract This article explores the evolution of strategic currents in management, highlighting the contributions of the normative, descriptive, and configuration schools, as well as the resource-based approach. The first part traces the emergence of corporate strategy in the 1960s, when companies adopted concepts from military strategy to meet the challenges of an increasingly competitive economy. The normative school emphasize a rational, prescriptive approach to strategic formulation, based on analysis of the external environment. In contrast, process schools emphasize the importance of organizational learning and intuition in the development of emerging strategies, offering a more descriptive perspective. The article also examines the configuration approach, which views organizations as dynamic entities that continually adapt to change. This holistic vision provides a better understanding of the diversity of strategies and organizational transformations. A comparison is then made between sector analysis, which focuses on competitive forces and key success factors, and the internal resources perspective, which values the company's unique and hard-to-imitate assets. The article highlights the limitations of traditional models, notably their lack of flexibility and their inability to explain innovative strategies. It proposes an integrative approach that combines adaptation to external pressures with proactive management of internal resources. Practical implications are discussed, suggesting that companies need to develop agile strategies to navigate a competitive and uncertain environment, while investing in their distinctive capabilities to maintain a sustainable competitive advantage. Key words: Corporate strategy, Porterian approach, Resource-based approach, Competitiveness, Dynamic capability.